'GP Live'- recorded General Practice consultations as a learning tool for junior medical students faced with the COVID-19 pandemic restrictions. Issue 6 (1st November 2020) - Dow, Naomi; Wass, Val; Macleod, David; Muirhead, Laura; McKeown, John
ABSTRACT: Background: First year medical students value doctor and patient contact. However, it can be challenging to achieve positive exposure to primary care on a large scale. The COVID-19 pandemic has placed even greater pressure on placing students in General Practice (GP). Aim: To assess the feasibility and acceptability of showing Year 1 medical students authentic recorded consultations between GPs and patients, and then explore what they gained from this. Method: Using Panopto® Video Platform, we pre-recorded real Primary Care consultations, with patient and GP consent, which were then processed securely using the University of Aberdeen server. These were shown to all Year 1 medical students who immediately debriefed these consultations in small groups with a GP tutor. Subsequently two focus groups were held with 11 students to evaluate what they had learnt. Learning outcomes: The consultations were easy to record and play during the teaching session, although there were some issues with sound quality. All students in the focus groups enjoyed the experience. They gained new knowledge about the skills of GPs, and recognised GPs as positive role models. Students were able to identify a variety of communication and consultation skills used by the GP, which reinforced their teaching on these delivered elsewhere in the course. Conclusion: Using pre-recorded consultations as a teaching tool is reproducible, time-efficient and beneficial to students. We propose that this model of using authentic 'live' interactions between GPs and patients represents a valuable undergraduate educational opportunity and could be utilised by medical schools internationally.